Influence of Portland cement alkalinity on wool-reinforced mortar. Issue 3 (6th June 2021) - Fantilli, Alessandro P.; Jóźwiak-Niedźwiedzka, Daria
Abstract : Natural wool is a good insulating material, both thermally and acoustically. With the increase in demand for the usage of waste materials, other applications have been found, such as the use of wool as a fibre reinforcement in mortars and concretes. Unfortunately, wool, like other natural organic materials, dissolves in alkaline environments and, consequently, the performance of wool reinforcement cannot be guaranteed for a long time. To address this issue, three series of wool-reinforced mortar beams, with various contents of alkalis in cement, were investigated. The chemical compatibility and the effects of alkalinity on mechanical performance were investigated by testing the beams under three-point bending and, subsequently, by analysing the microstructure of the mortars using energy-dispersive X-ray spectroscopy. The results showed that the lower the alkalinity of the cement paste, the better the resistance of wool fibres in the cementitious matrix, thus guaranteeing larger post-cracking residual stresses in the wool-reinforced mortars.